Psychodrama technique in enhancing communications skills among Special Education Integration Program (SEIP) students in Malaysia: a case study - Siti Khadijah Hashim; Abu Yazid Abu Bakar (Indonesian Institute for Counseling, Education and Theraphy, 2020)
This study aimed to determine the effectiveness of psychodrama technique in enhancing social interaction among Special Education Integration Program (SEIP) students in Malaysia. The objectives of the study were to train SEIP students to communicate well through psychodrama, to increase self-confidence when communicating and to expose students to self-management through psychodrama. The study was conducted via group session on a psychoeducational program involving 13 students with different learning disabilities at Sekolah Kebangsaan Taman Seri Mawar, Negeri Sembilan. The results show that SEIP students knew the knowledge on how to manage themselves but still need to be improved in terms of communication skills and social interaction in groups.